The amount of knowledge in Iranian female adolescents student about osteoporosis and its risk factors - Mirzaaghaee F; Moinfar Z; Eftekhari S; Karimi Khezri M; Mazidi M; Aliramezani M; Sedaghat M (Tehran University of Medical Sciences, 2006)
Background & Aim: Osteoporosis is a metabolic disease which is the result of gradual destruction of bone mass and its most serious and frequent complication is hip fracture. Because adolescent females are the high risk group of affecting this disease, the purpose of this study was to assay female students' knowledge's about osteoporosis and its risk factors. Methods & Materials: A cross-sectional study with a 31-item questionnaire was used in this research. A convenience sample of 1000 adolescents in grade 1-3 who attended at 6 high schools participated in this study. Using SPSS software, the data were analyzed by chi2 and T tests. Results: According to 22 questions about knowledge, sufficient knowledge of students was estimated 40.8%. Among 10 factors related to the family, only correlation between father occupation and knowledge was significant statically (p=0.049). Knowledge was higher in independent- medicine versus dependent medicine occupations. Conclusion: Overall, the knowledge of these assayed female students about this disease and its risk factors including sex, race, smoking, sun exposure, exercise, calcium- rich foods and menopause and its complications was limited.